Language institutions and language criticism in German - Jacob, Katharina; Schwinn, Horst (Handbuch europäische Sprachkritik online, 2019)
With the exception of the Council for German Orthography, there is no German governmental institution with a political mandate to legitimately provide support for a linguistic standardisation of a national language. Against this backdrop, this article will examine the various non-governmental German-language linguistic institutions. In the German-speaking regions, the language academies of neighbouring countries have always served as a model; however, the linguistic societies and language associations that have been established have primarily been devoted to language cultivation.
Gesehen am 29.06.2020